Optimized Operation of a Two-Tier Game for Community-Based Integrated Energy Systems Considering Stepwise Carbon Trading and Integrated Demand Response - Wang, Xuebin; Fu, Guobin; Cheng, Yufeng; Song, Rui; Cui, Yang; Fu, Dazhi; Zhu, Fu; Jiang, Shuai (2023 IEEE 7th Conference on Energy Internet and Energy System Integration (EI2), 2023)
In this paper, we propose a multi-subject game co-optimization method considering the stepped carbon trading mechanism and integrated demand response strategy for the problem of conflicting interests of multiple subjects in community integrated energy system. In this paper, the particle swarm algorithm is improved while considering the stepped carbon trading mechanism on both the source and load sides and the integrated demand response on the load side. First, the community integrated energy system considering stepped carbon trading mechanism and integrated demand response is modeled. Second, a master-multiple-slave Stackelberg model is built with the integrated energy retailer(IER) as the leader and the integrated energy provider(IEP), user aggregator, and energy storage service operator(ESO) as the followers. Finally, an improved particle swarm method based on Gaussian perturbation and chaotic mapping with cplex solver is used to solve the model in this paper. The simulation results verify the effectiveness of the multi-subject collaborative optimization model proposed in this paper.